2007
DOI: 10.3108/beej.10.c3
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Self-Directed Learning — the Importance of Attitudes and Skills

Abstract: The use of Self-Directed Learning (SDL) as a learning tool is increasing in today's educational environment, especially in medical schools. We wanted to examine whether all students are effective self directed learners and can make use of this learning tool to achieve learning objectives. Students (n = 125) of first-year medical training program were selected and for a period of 10 weeks they were exposed to two types of teaching programs i.e. SDL sessions and regular didactic lectures. Based on the total sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
0
10
1
4
Order By: Relevance
“…Penelitian terdahulu terkait efektivitas SDL telah pernah dilakukan SDL dianggap sebagai suatu metode pembelajar dewasa, tujuan dalam proses pembelajaran, berdampak positif terhadap pencapaian hasil belajar mahasiswa, dan menyarankan agar SDL menjadi salah satu metode alternatif dalam proses pembelajaran (Bhat, Rajashekar, & Kamath, 2007;Carvalho, Souza, Takiguti, & D, 1977;Graham, Seabrook, & Woodfield, 1999;Mahmoud, Andrus, Matolo, & Ward, 2006;Owen, Byrne, & Ker, 2008;Schneeweiss & Ratnapalan, 2007;Vidal et al, 2001). Beberapa peneliti yang lain menemukan bahwa mahasiswa kedokteran dan keperawatan yang telah terlibat dalam kurikulum terintegrasi dengan pendekatan PBL memiliki kemampuan SDL yang tinggi dibandingkan dengan kemampuan SDL mahasiswa umum (Guglielmino, L.M.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Penelitian terdahulu terkait efektivitas SDL telah pernah dilakukan SDL dianggap sebagai suatu metode pembelajar dewasa, tujuan dalam proses pembelajaran, berdampak positif terhadap pencapaian hasil belajar mahasiswa, dan menyarankan agar SDL menjadi salah satu metode alternatif dalam proses pembelajaran (Bhat, Rajashekar, & Kamath, 2007;Carvalho, Souza, Takiguti, & D, 1977;Graham, Seabrook, & Woodfield, 1999;Mahmoud, Andrus, Matolo, & Ward, 2006;Owen, Byrne, & Ker, 2008;Schneeweiss & Ratnapalan, 2007;Vidal et al, 2001). Beberapa peneliti yang lain menemukan bahwa mahasiswa kedokteran dan keperawatan yang telah terlibat dalam kurikulum terintegrasi dengan pendekatan PBL memiliki kemampuan SDL yang tinggi dibandingkan dengan kemampuan SDL mahasiswa umum (Guglielmino, L.M.…”
Section: Pendahuluanunclassified
“…Hasil penelitian yang lain menunjukkan bahwa SDL memberikan kontribusi terhadap peningkatan moderat pada pencapaian hasil belajar mahasiswa baik dalam domain pengetahuan maupun domain keterampilan (Bhat, Rajashekar, & Kamath, 2007;Considine, Botti, & Thomas, 2005;Mahmoud, Andrus, Matolo, & Ward, 2006;Murad, Coto-Yglesias, Varkey, Prokop, & Murad, 2010;Owen, Byrne, & Ker, 2008;Schneeweiss & Ratnapalan, 2007). Asumsi yang dapat diberikan terkait dengan hasil penelitian ini yaitu, pertama, mahasiswa yang menjadi responden dalam penelitian ini memiliki kemampuan akademik yang cenderung sama.…”
Section: Pembahasanunclassified
“…Whilst self-directed learning may have a number of advantages, its shortcomings cannot be overlooked. According to a recent study, self-directed learning is not an effective learning tool for all students (Bhat, Rajashekar, & Kamath 2007). This study demonstrates that self-directed learning could benefit some students to understand concepts but other students lacking the requisite cognitive skills might suffer.…”
Section: The Limitation Of Self-directed Learningmentioning
confidence: 76%
“…By hybrid curriculum is meant a curriculum that combines traditional teaching methods and PBL aiming to benefit from advantages of the innovative learning strategy [8,20]. Besides curriculum approach, there is no common consensus between the correlation of sociodemographic factors such as curriculum year, age, and academic achievement and students' SDL [21][22][23][24][25][26][27][28]. Leatemia et al [25] revealed higher level of SDL readiness in first-year students compared to second-year medical students of a hybrid PBL curriculum.…”
Section: Introductionmentioning
confidence: 99%